Bridging civil society in electronic government participation: a case study in Majlis Perbandaran Sungai Petani Kedah (MPSPK) / Nazni Noordin, Zaherawati Zakaria, Hadzli Ishak - Noordin, Nazni; Zakaria, Zaherawati; Ishak, Hadzli (Institute of Research Management & Innovation (IRMI), 2013)
Malaysia’s electronic government (e-government) is one of the efforts taken by Malaysian Government in order to improve the quality of service provided to public. The aim of introducing e-government by public organization is to help public lessen their burden and time consumption to manage their transactions. However, most of the public resist to fully participate in e- government application due to the lack of reliability and some other reasons as perceived by the public. As to Majlis Perbandaran Sungai Petani Kedah (MPSPK), this local government also facing the same issue. The purpose of this study is to identify what factors contributed to this phenomenon and what is the most factor contributed to this issue. By using simple random technique, 489 residents, which cover one percent of total residents in MPSPK, were selected as respondent for this study. The finding indicated that out of six applications of e- government by MPSPK, none achieved 50% of usage, the highest only 34.1%, which is e-borang MPSPK. On top of that, among three independent variables that tested, which is, security and privacy of e- government application, attitudes of residents towards participation in e-government and effectiveness of e-government, the most dominant factor was attitude of residents. This outcome may assist the management of MPSPK in creating some strategic planning on how to persuade public to actively participate in e- government application provided by them. Otherwise the government spending on this e-government application will go waste and just look nice on paper only. This will have retarded our vision to be fully developed country by year 2020.